Internazionalizzazione e competitività delle imprese produttrici di macchine utensili: alcune evidenze empiriche - Cerrato, Daniele; Depperu, Donatella (Piccola Impresa / Small Business, 2010)
This paper is based on the empirical analysis on a sample of 33 producers of machine tools. The aim is to explore firms’ international strategies and the characteristics of their presence in foreign markets from both a qualitative and quantitative point of view. The survey relies on data collected through a questionnaire submitted to the firms belonging to UCIMU (the Association of Italian Manufacturers of Machine Tools, Robots, Automation Systems) and through a number of face-to-face interviews with entrepreneurs. The central role of internationalization within the firms’ patterns of growth is the first relevant finding of the study: in the period 2003-2006 firms’ growth was driven by foreign markets. Firms show high levels of both export intensity and geographical scope. They mainly rely on export as entry mode in foreign markets. Firm size only partially explains the choice of internationalization strategies characterized by low commitment. In fact, the shift from indirect export towards entry modes based on greater commitment and investments requires not only more financial resources, but also a significant organizational and managerial development. Our analysis shows that the level of human capital (for example, the number of managers with international experience in their professional background and the number of graduate employees), management competencies, and competitive advantages based on innovation and quality affect the degree of international development of the firms. These factors are fundamental for those firms that aim at strengthening their presence in foreign markets, especially emerging ones.